Construction of Schottky junction solar cell using silicon nanowires and multi-layered graphene. (February 2019) - Lin, Yu-Keng; Hong, Yu-Ting; Shyue, Jing-Jong; Hsueh, Chun-Hway
Abstract: Schottky junction solar cells based on n-type silicon nanowires (SiNWs) and multi-layered graphene were assembled. The textured substrates enhanced the light-harvesting compared to the planar substrates. Multi-layered graphene films produced by chemical vapor deposition and layer-by-layer stacking mitigated damages and increased the work function of graphene. Thus, both the power conversion efficiency and fill factor of Schottky junction solar cells could be improved with multi-layered graphene. It was found in the present study that the optimum photovoltaics performance of solar cells was achieved when double-layered graphene was used. The performance degraded with the number of graphene layers when it was more than 2 layers. While damages could be mitigated and the work function could be improved using multi-layered graphene in SiNWs Schottky junction solar cells, the optical transmittance of graphene would be reduced with excessive number of graphene layers. Graphical abstract: Image 102541 Highlights: We used metal-assisted chemical etching to form Si nanowires. Use Si nanowires and multi-layered graphene to make Schottky junction solar cell. Layer-by-layer stacking ensures better coverage of graphene on silicon nanowires. Optimum photovoltaics performance is achieved for bi-layered graphene device.